A time of change - Thurlo, Aimée (Forge, 2013)
"A Time of Change is a perfect example of the Thurlos's ability to combine passion with tension as they introduce readers to Josephine Buck and other employees at a New Mexico trading post. When The Outpost's owner dies, Josephine, a young Navajo woman, is shocked to discover that Tom Stuart, whom she thought of as a surrogate father, has left her the business. Ben Stuart and his dad had had problems, but military service changed Ben for the better and put the two men back in each other's lives. His father's sudden death ends any possibility of a true reconciliation and leaves Ben fuming at being disinherited. Suspecting that Jo had an affair with his father, Ben is determined to get control of the trading post. Jo's hataalii training shows her that Ben is wounded in both body and soul, and she becomes determined to help him. As Jo and Ben move toward a deeper understanding of each other, they learn that Tom Stuart was murdered and that the trading post at the center of their lives holds many secrets"--